Histology and biogenic amines localization of salivary gland of the adult Red Palm Weevil, Rhynchophorus ferrugineus (coleoptera: dryophthoridae) - Norzainih J.J.,; Nurul Wahida Othman,; Norefrina Shafinaz Md Nor, (Pusat Sistematik Serangga ,UKM, 2016)
This study describes the histology and biogenic amines localization of salivary glands of the adult Red Palm Weevil (RPW), Rhynchophorus ferrugineus. The observation were done by using light microscopy of Zeiss Image Analyzer with Axio Vision software and Zeiss Axioscope with iSolutionlite software. The histology involves staining procedures of haematoxylin and eosin staining method while the immunohistochemistry analysis involves serotonin and dopamine of the biogenic amines. The salivary gland of the RPW adult is a single tubular gland. The single gland lies dorsally on the alimentary tract of the insect that begins in the head and extends through the thorax into the abdomen. The reservoir region is located in the mid to fore region of the gland, while the secretary region is found in the mid to rear part of the gland. The reservoir region of the RPW tubular gland seems to probably secrete only water and ions but do not secrete enzymes. The distribution of biogenic amines suggest that dopamine mainly stimulates the production of water-based saliva in the secretory cells of the reservoir region, while serotonin stimulates the production of protein-rich saliva in the secretory cells of the secretory region.